Impact of perioperative pain management on cancer recurrence: an ASRA/ESRA special article. Issue 1 (January 2019) - Missair, Andres; Cata, Juan Pablo; Votta-Velis, Gina; Johnson, Mark; Borgeat, Alain; Tiouririne, Mohammed; Gottumukkala, Vijay; Buggy, Donal; Vallejo, Ricardo; Marrero, Esther Benedetti de; Sessler, Dan; Huntoon, Marc A; et al.
Abstract : Cancer causes considerable suffering and 80% of advanced cancer patients experience moderate to severe pain. Surgical tumor excision remains a cornerstone of primary cancer treatment, but is also recognized as one of the greatest risk factors for metastatic spread. The perioperative period, characterized by the surgical stress response, pharmacologic-induced angiogenesis, and immunomodulation results in a physiologic environment that supports tumor spread and distant reimplantation.In the perioperative period, anesthesiologists may have a brief and uniquewindow of opportunity to modulate the unwanted consequences of the stressresponse on the immune system and minimize residual disease. This reviewdiscusses the current research on analgesic therapies and their impact ondisease progression, followed by an evidence-based evaluation of perioperativepain interventions and medications.